Deletion in the short arm of the X chromosome in a patient with secondary amenorrhea: Case report [X kromozomunun kisa kolunda delesyon ile seyreden sekonder amenore: Olgu sunumu] - (:unkn) unknown (My University, 1997)
Premature ovarian failure (POF) is defined as cessation of menses before age 40. Besides sex chromosome anomalies such as 45,X, 47,XXY and mosaicism, deletions in the short or long arms of the X chromosome may result in POF. In addition it may be secondary to an autoimmune process, mumps oophoritis, radiation or chemotherapy. We present a case of POF associated with deletion in the short arm of the X chromosome (46, X, del (X) (p11-pter)) in this report.
Keywords: amenorrhea; X chromosome